Residual stresses explaining clinical fractures of bilayer zirconia and lithium disilicate crowns: A VFEM study - Rodrigues, Camila S. [UNESP]; Dhital, Sukirti; Kim, Jeongho; May, Liliana Gressler; Wolff, Mark S.; Zhang, Yu (Elsevier, 2021)
Objective: To understand the stress development in porcelain-veneered zirconia (PVZ) and porcelain-veneered lithium disilicate (PVLD) crowns with different veneer/core thickness ratios and cooling rates. To provide design guidelines for better performing bilayer restorations with the aid of Viscoelastic Finite Element Method (VFEM). Methods: The VFEM was validated by comparing the predicted residual stresses with experimental measurements. Then, the model was used to predict transient and residual stresses in the two bilayer systems. Models with two different veneer/core thickness ratios were prepared (2:1 and 1:1) and two cooling protocols were simulated (Fast: ∼300 °C/min, Slow: ∼30 °C/min) using the heat transfer module, followed by stress analysis in ABAQUS. The physical properties of zirconia, lithium disilicate, and the porcelains used for the simulations were determined as a function of temperature. Results: PVLD showed lower residual stresses than PVZ. The maximum tensile stresses in PVZ were observed in the cusp area, whereas those in PVLD were located in the central fossa. The 1:1 thickness ratio decreased stresses in both layers of PVZ. Slow cooling slightly decreased residual stresses in both systems. However, the cooling rate effect was more evident in transient stresses. Significance: Slow cooling is preferable for both systems. A thinner porcelain layer over zirconia lowers stresses throughout the restoration. The different stress distributions between PVZ and PVLD may affect their failure modes. Smaller mismatches in modulus, CTE, and specific heat between the constituents, and the use of low Tg porcelains can effectively reduce the deleterious transient and residual tensile stresses in bilayer restorations.
Keywords: Bilayer crowns; Coefficient of thermal expansion; Cooling rate; Dental ceramics; Elastic modulus; Residual stress; Specific heat; Transient stress